Research in Mindfulness Interventions for Patients With Fibromyalgia: A Critical Review - Leça, Salomé; Tavares, Isaura (Frontiers in Integrative Neuroscience, 2022)
Fibromyalgia is one of the most common causes of widespread chronic pain. It has a huge impact on the quality of life, namely because it appears earlier in life than most of the chronic pain conditions. Furthermore, emotional-cognitive distress factors, such as depression and anxiety, are a common feature in patients with fibromyalgia. The neurobiological mechanisms underlying fibromyalgia remain mostly unknown. Among non-pharmacological treatments, cognitive-behavioral therapy has been used during the last decade, namely with the enrolment of patients in programs of mindfulness-based stress reduction (MBSR) and in mindfulness-based interventions (MBI). We critically analyzed the literature to search for scientific evidence for the use of MBI in fibromyalgia. The studies were evaluated as to several outcomes of fibromyalgia improvement along with aspects of the study design which are currently considered relevant for research in mindfulness. We conclude that despite the sparsity of well-structured longitudinal studies, there are some promising results showing that the MBI are effective in reducing the negative aspects of the disease. Future design of studies using MBI in fibromyalgia management should be critically discussed. The importance of active controls, evaluation of sustained effects along with investigation of the subserving neurobiological mechanisms and detailed reports of possible adverse effects should be considered.